Exploring Factors Influencing Fear of Crime in a Relatively Small Urban Setting of a Developing Country - Cinoglu, Huseyin; Odabasi, Mehmet (European Scientific Journal, ESJ, 2023)
The prevailing trend in fear of crime research revolves around using data predominantly sourced from major cities in developed nations. Unfortunately, this particular method greatly limits the relevance and universality of these investigations when it comes to smaller urban areas and developing nations. The aim of this study is to fill that gap in the literature. It focuses on three key factors: demographic characteristics, prior victimization, and neighborhood structure. The study was conducted in Elazığ, Turkiye, with 430 participants. Survey questions included Likert-type items. Fear of Crime scale provided a score of 2.37 which is very close to the notion of “not worried.” Hypotheses are tested using the Independent Samples T-Test, ANOVA, and correlation tests. According to the results, fear of crime was found to be higher for female participants compared to males, for people with no formal education compared to people with higher education, for people with prior victimization compared to people with no prior victimization, and for people who perceive neighborhood unity compared to people who think otherwise.